2011
DOI: 10.1007/s10750-011-0968-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shallow and deep sediment disturbance on whole-stream metabolism in experimental sand-bed flumes

Abstract: Water flow causes complex patterns of sediment disturbance in sand-bed streams, but effects on stream metabolism resulting from different depths of sediment scour and fill are poorly known. We assessed such effects by manually disturbing sandy sediments of 16 experimental outdoor flumes to two different depths (1 and 4 cm) during an early and a more advanced stage of stream community succession. To separate effects on heterotrophic and autotrophic metabolism, half of the flumes were permanently covered. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…comparably low flow causing sand ripple migration [Baas, 2003]. Gerull et al [2012] found that a single disturbance of a sand bed in flumes did not affect respiration of the microbial community. The sediment in these flumes was disturbed once only by mixing the upper 1 cm of the sand bed, generating a mechanical disturbance that was similar in depth and nature to the disturbance during one cycle of sediment shift in migrating sand ripples.…”
Section: 1002/2017wr020656mentioning
confidence: 99%
“…comparably low flow causing sand ripple migration [Baas, 2003]. Gerull et al [2012] found that a single disturbance of a sand bed in flumes did not affect respiration of the microbial community. The sediment in these flumes was disturbed once only by mixing the upper 1 cm of the sand bed, generating a mechanical disturbance that was similar in depth and nature to the disturbance during one cycle of sediment shift in migrating sand ripples.…”
Section: 1002/2017wr020656mentioning
confidence: 99%
“…After inoculation, the stream channels ran in complete recirculation mode for 24 h with filtered (5 μm pore size) Chicken Creek water to facilitate establishment of the added microorganisms. Subsequently, the channels received well‐oxygenated groundwater from a subterranean tank (Gerull et al ., ) to replace 5% of the water volume during each cycle in the now partially recirculating channels. The current velocity was 1.7 ± 0.3 cm s −1 at a water depth of 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a full factorial experiment in outdoor channels simulating early-successional sand-bed streams. The channels (4.0 ¥ 0.12 ¥ 0.12 m) were set up next to a recently created experimental catchment (referred to as Chicken Creek) near Cottbus in eastern Germany (51°36′N, 14°16′E) situated in a former brown-coal mining area (Gerwin et al, 2009;Gerull et al, 2012). The channels were filled with a 4 cm layer of sterilized (combustion overnight at 160°C) sandy sediment collected from a dry stream reach in the catchment and supplied with well-oxygenated groundwater originating from the catchment.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). Dissolved organic carbon (DOC) was abundant, averaging 9.8 mg L À1 , but hardly bioavailable (Gerull et al, 2012). This ensured natural light, temperature and other environmental conditions.…”
Section: Experimental Designmentioning
confidence: 99%